Esthetic Foundations of Politics in the Conception of Wilhelm von Humboldt - Chmieliński, Maciej (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The article examines the esthetic conception of self-cultivation (Bildung), which is the key idea of the political thought of Wilhelm von Humboldt, one of the most important representatives of German idealism and pre-Romanticism. Conceptions of pre-Romanticism and Romanticism have brought new, revolutionary paradigm of an artistic activity. Unlike the classical concepts (e.g. Plato), which generally saw art as an imitation of nature, the pre-Romantic and Romantic conceptions have started to interpret art primarily as an expression of an artist’s originality and individuality. The starting point for this change of esthetic paradigm was surprisingly the Kantian philosophy of the subject, interpreted in a radical manner by German pre-Romantics and Romantics. In Humboldt’s thought, the new, esthetic and individualist paradigm creates foundations for the classical, liberal conception of the minimal state. Therefore, the esthetic conception of self-cultivation became the very foundation of Humboldt’s political philosophy.